Salute to Semyon M. Hertz (1947-2020), an outstanding engineer-radio physicist, his social life and contribution to photosynthetic science - Karl Y Biel; Irina R Fomina (Open Journal of Biological Sciences - Peertechz Publications, 2021)
The article is dedicated to the memory of Semyon M. Hertz, a talented radiophysicist engineer and remarkable person who left us prematurely at the age of 74. He devoted most of his scientific activities to biology, primarily phototrophic organisms, using radionuclide substances. The main achievements in the study of photosynthesis made thanks to his physical and mathematical calculations and engineering developments, are described. The ability to overcome difficulties, fortitude, vitality, and optimism of Semyon Hertz were noted.